Družbeno porazdeljena kognicija - Ule, Andrej (Družboslovne razprave, 2008)
I present some alternatives to the predominant 'monadic' paradigm of cognition that we can summarise in the slogans 'society in mind/society of mind' and which complement the well-known slogan 'mind in society'. I first present Minsky's idea of the human mind as a kind of society in a small degree (society of mind) that works on the basis of parallel-distributed processes among interlinked mental agents. I then present the concepts of socially distributed cognition, Hutchinćs theory of 'distributed cognition' and the basis of the formal-logical models of distributed cognition concepts of collective intentionality and rationality. We have to complement these concepts with the concepts of collective intentionality, collective rationality and social epistemology and finish with some unsolved theoretical problems concerning socially distributed cognition.
Keywords: Kognitivna znanost; Cognitive science; Filozofija; Philosophy; Sociologija spoznavanja; Sociology of cognition; znanje; knowledge